2010
DOI: 10.1016/j.humpath.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma: correlation of KIT expression with survival and evaluation of KIT gene mutational status

Abstract: Merkel cell carcinoma is one of the most aggressive primary cutaneous malignancies. Since some Merkel cell carcinomas express the receptor tyrosine kinase KIT, we aimed to evaluate the correlation of KIT expression with outcome and the presence of activating mutations in the KIT gene in Merkel cell carcinoma. A total of 49 tumors from 40 patients with a diagnosis of Merkel cell carcinoma were identified of which 30 cases from 21 patients were used in the study. KIT expression was assessed by immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 38 publications
6
37
1
1
Order By: Relevance
“…In addition, we did not detect any mutations in 4 MCC cell lines that contain MCPyV. Consistent with previous studies, we did not find activating muta tions in PDGFRA or KIT (23,(35)(36)(37)(38). We did identify 3 tumors with p53 point substitutions, most notably in 2 specimens with absent expression of MCPyV large T antigen.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we did not detect any mutations in 4 MCC cell lines that contain MCPyV. Consistent with previous studies, we did not find activating muta tions in PDGFRA or KIT (23,(35)(36)(37)(38). We did identify 3 tumors with p53 point substitutions, most notably in 2 specimens with absent expression of MCPyV large T antigen.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our results are in concordance with observations in Merkel cell carcinoma (Andea et al 2010), colorectal neuroendocrine carcinoma (Akintola-Ogunremi et al 2003) and squamous cell lung cancer (Micke et al 2004), with the two former showing only a trend to shorter survival and the latter exhibiting a significant value. Before our immunohistochemical analysis, we examined the KIT and PDGFRA staining pattern on standard, full-sized tissue sections and could not see a intratumoral heterogeneity supporting our results.…”
Section: Discussionsupporting
confidence: 92%
“…This is a smaller number of positive cases than that reported previously in neuroendocrine carcinoma of the skin, in Merkel cell carcinoma (62%) (Andea et al 2010). This might be due to the fact that our tumor collective included not only poorly differentiated carcinomas (NEC 3, high grade), but also well-differentiated tumors (NET G2, intermediate grade 2) and well-differentiated tumors (NET G1, low grade).…”
Section: Discussioncontrasting
confidence: 63%
“…KIT tyrosine kinase receptor (c-kit) or CD117 expression has also been investigated to identify the association with prognosis, but no association was found in most studies [29,57,63,64]. Recently, Andea et al [65] reported that MCCs with high KIT expression showed worse 5-year survival than those with low (or negative) KIT expression, although the difference did not reach statistical significance (P = .07). Several previous studies found no activating mutations in a hot spot of the KIT gene in MCCs with high KIT expression, suggesting little or no involvement of KIT in the progression of MCC and the ineffectiveness of imatinib mesylate as a treatment of MCC [61,[65][66][67][68].…”
Section: Immunohistochemistry Of Prognostic Markersmentioning
confidence: 99%